COVID-19 BANNER: JAVANESE LANGUAGE EXPRESSION FUNCTION TO FACE THE PANDEMIC (SPANDUK COVID-19: FUNGSI UNGKAPAN BAHASA JAWA UNTUK MENGHADAPI PANDEMI) - Ramadani Eki Cahyo Putri; Muhammad Rozin; Sharifah Nur Afiqah (Universitas PGRI Sumatera Barat, 2021)
The Covid-19 issue has become an issue highlighted across the world's media in recent months. In this case, the public needs correct and credible information to prevent wider transmission. One way to do this is by using Banners that attract people's attention. This paper aims to describe the role of the Covid -19 Banners in increasing public awareness of the emergence of Covid-19 by using a sociolinguistic perspective. The study found that Banners are an important way to reduce the number of Covid-19 emergencies because it is seen as an emergency social warning that the public believes in. The emergence of the Covid-19 Banners presented in many languages aims to make a closer approach to the target community so that it functions properly. These Banners are made so that we can use them to deliver particular messages to the addressee. The method used is descriptive qualitative, where the researchers used contextual techniques to consider social, situational, and cultural aspects background. After being analyzed, those Banners brought at least five functions, informational, expressive, directive, aesthetic, and phatic functions. Those functions are well discussed here by referring to each social context it is attached. The analysis then goes to its sociolinguistics aspects. The use of Javanese covid-19 Banners here aims to create a bonding between Banners makers and the addressee, for those belonging to a certain speech community will feel that these Banners content are worth noticing